2012
DOI: 10.1021/jp210479a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical TiO2 Nanoflakes and Nanoparticles Hybrid Structure for Improved Photocatalytic Activity

Abstract: Three-dimensional TiO 2 microspheres with different hierarchical nanostructures were synthesized by the synergistic strategies of ultrafast electrochemical spark discharge spallation process followed by thermal treatment. The morphology, crystal structure, surface area, and photocatalytic activity of the hierarchical nanostructures were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, surface area analysis, and UV−vis spectroscopy respectively. The nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 59 publications
0
104
0
Order By: Relevance
“…Meanwhile, a broad prominent absorption in the visible light region of 450-600 nm was observed in Ag@AgCl-based composites, which could be attributed to the surface plasmon resonance (SPR) effect of Ag [26][27][28]. The surface plasmon absorption on the surface of Ag derives from a collective oscillation of free electrons excited by the matching photon energy.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Meanwhile, a broad prominent absorption in the visible light region of 450-600 nm was observed in Ag@AgCl-based composites, which could be attributed to the surface plasmon resonance (SPR) effect of Ag [26][27][28]. The surface plasmon absorption on the surface of Ag derives from a collective oscillation of free electrons excited by the matching photon energy.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Nanoflakes are a special class of nanomaterials that are characterized to possess high photocatalytic activity under visible light irradiation when compared to their pure form nanoparticles due to the changes in optoelectronic properties (Tang et al 2012;Zhang et al 2011) These nanoflakes can be prepared by alkaline or at low-temperature hydrothermal techniques. Ong et al (2013) reported the photocatalytic degradation of methyl orange by metalloaded ZnO nanoflakes.…”
Section: Nanoflakesmentioning
confidence: 99%
“…Ong et al (2013) reported the photocatalytic degradation of methyl orange by metalloaded ZnO nanoflakes. Tang et al (2012) reported the improved photocatalytic degradation of methyl orange and bisphenol by hierarchical TiO 2 nanoflakes.…”
Section: Nanoflakesmentioning
confidence: 99%
“…The prominent absorption band in the visible-light region could be attributed to the surface plasmon resonance (SPR) effect of Ag. Meanwhile, a broad prominent absorption in the visible-light region of 450-800 nm was observed in Ag@AgBr-based composites, which could be attributed to the surface plasmon resonance (SPR) effect of Ag [24][25][26]. The surface plasmon absorption on the surface of Ag derives from a collective oscillation of free electrons excited by the matching photon energy.…”
Section: Catalyst Characterizationmentioning
confidence: 99%